Role played by the physical training specialist in the Program of Cardiac Rehabilitation - Reinol Hernández González; Eduardo Rivas Estany; Ismaris Núñez Hernández; Juan A. Álvarez Gómez (ECIMED, 2014)
Some of the positive effects of physical exercise on patients suffering from heart disease, such as the increase of functional capacity in women and patients classified as high risk, the improvement of heart rate and arterial pressure, etc., are mentioned here. The objective of this paper was to explain the functioning of the section of physical training within the cardiac rehablitation programs. The functioning of this section at the Rehabilitation Center of the Cardiology Institute of Havana, as well as the leading role played by the physical training specialist in the cardiac rehabilitation were explained. To conclude, it was determined that in the cardiac rehabilitation programs there will always be a physical training specialist with the necessary knowledge to guarantee patient?s health and safety.